Perception of Altered Smile Esthetics by Orthodontists, Dentists, and Laypeople in Riyadh, Saudi Arabia - Aldeeri AA; Alhababi KA; Algahtani FA; Tounsi AA; Albadr KI (Dove Medical Press, 2020)
Arwa Ahmed Aldeeri,1 Khaled Abdullah Alhababi,2 Fahad Abdullah Algahtani,3 Abrar Abdullah Tounsi,4 Khalid Ibrahim Albadr5 1Orthodontics and Dentofacial Orthopedics, King Saud University, Riyadh, Saudi Arabia; 2Dental Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 3Orthodontics and Dentofacial Orthopedics, King Saud Medical City, Riyadh, Saudi Arabia; 4Department of Periodontics and Community Dentistry, King Saud University, Riyadh, Saudi Arabia; 5Orthodontic Department, Prince Sultan Military Medical City, Riyadh, Saudi ArabiaCorrespondence: Arwa Ahmed Aldeeri Tel +966-53-900-4403Email ArwaAldeeri@gmail.comBackground: Mini-esthetics is an important concept in orthodontics concerned with relatedness of dentition to the face.Purpose: We compared the perception of altered smile esthetics between orthodontists, dentists, and laypeople in Riyadh, Saudi Arabia.Patients and Methods: A total of 216 participants (orthodontists, dentists, and laypeople) were conveniently surveyed. An image representing the ideal smile was altered in terms of buccal corridor, gingival display, and midline diastema. Using Likert scale, participants were asked to rate the attractiveness of the altered images.Results: The three surveyed groups preferred wide rather than narrow buccal corridors. Also, as the amount of gingival display and midline diastema increased, the smile was rated less attractive. Age of participants was significantly associated with more precise recognition of gingival display and midline diastema, P< 0.05 and P< 0.001, respectively.Conclusion: The concept of an ideal smile holds true across the heterogenous groups we studied despite gender and professional background.Keywords: dentistry, orthodontics, smile, beauty